Terahertz ribbon waveguide for sensing electrolyte concentration in phosphate-buffered saline solution - Ja-Yu Lu; Pin-Jung Lu; Borwen You (Sensing and Bio-Sensing Research)
A subwavelength-thick porous ribbon waveguide (PRW) has been experimentally demonstrated for sensing biological electrolytes in the terahertz (THz) regime. The transmission loss constant of the transverse-magnetic (TM) waveguide mode propagating on a PRW is used as the THz sensing signal and found to be linearly responded to the quantity of electrolytes adsorbed in the PRW core in the measurement of THz time-domain spectroscopy. The propagation-loss change arising from the spatial confinement of the TM waveguide mode can be altered by variations in thickness and refractive-index of the electrolyte-filling PRW core. These findings were verified using the response curve of the THz sensing signal and the one-dimensional modal power distribution in both measurements and simulations. The detection sensitivity of the PRW-based sensing platform was experimentally demonstrated to achieve 0.092 cm−1/(μg/mm2) with an electrolyte-field interaction length of merely 1 cm. The limit of detection for sensing molar concentration changes of electrolytes in phosphate-buffered saline solutions was 23.52 mM within the detectable concentration range of 0.15–1.52 M, corresponding to a molecular density change as low as 18.18 nmol/mm2. The sensing performance significantly surpasses that of other THz sensing technologies. The simple and cost-effective PRW-based sensing approach enables efficient detection of trace analytes over a short interaction length, which is the critical feature to be well-suited for various biochemical sensing applications.